Evaluation of the quality of health and safety services with SERVPERF and multi-attribute decision-making methods - Alp, Selcuk; Yilmaz, Fatih; Gecici, Ebru (TAYLOR & FRANCIS LTD, 2022)
Evaluating the quality of occupational safety and health (OSH) services by experts is essential for both employee health and workplace productivity. In this study, first, the quality of OSH services is evaluated with a questionnaire using the SERVPERF method. Then, a questionnaire prepared according to the analytic hierarchy process (AHP) method is applied to OSH experts and the relative importance of the main dimensions and items in the SERVPERF method are determined. The weights of the items in the SERVPERF method are calculated with the AHP and fuzzy-analytic hierarchy process (FAHP). The quality scores obtained by the SERVPERF, AHP and FAHP methods are analyzed comparatively. The results show that the work environment-related measures and physical facilities in the workplaces are more inadequate, whereas assurance and empathy are better. Moreover, the items with the lowest value in the SERVPERF method get the highest score in the AHP and FAHP.
Keywords: SERVPERF; analytic hierarchy process; fuzzy-analytic hierarchy process; safety; quality; multi-attribute decision-making; FUZZY; PERCEPTIONS; SYSTEMS; MODEL; SATISFACTION; HOSPITALS; LOYALTY; Engineering; Public, Environmental & Occupational Health